Improvement Tanah Pasir Pantai Dengan Penambahan Tanah Lempungan Untuk Media Tanam Bibit Kelapa Sawit Di Pre Nursery - Ryan Firman Syah ryan (Universitas Merdeka Madiun, 2023)
Abstract—This research aims to determine the interaction between clay soil and organic material on the growth of oil palm seedlings in the pre-nursery, determine the best dose of clay for the growth of pre-nursery oil palm seedlings and determine the best dose of green fertilizer for the growth of oil palm seedlings in the pre-nursery on soil sand beach. This research was carried out at KP2 Kalikuning INSTIPER Yogyakarta, which is located in Wedomartani Village, Depok District, Sleman Regency, Yogyakarta Special Region Province, which was carried out in February-May 2023. The research method used a factorial pattern with a two-factor Completely Randomized Design (RAL). The first factor, clay dosage, consists of 4 classifications, namely 0 g, 100 g, 150 g, and 200 g. The second factor is green manure dosage, which consists of 4 classifications, namely 0 g, 50 g, 75 g, and 100 g. From these two factors, 16 treatment combinations were obtained, and each treatment had 3 replications, so the total number of plants in this study was 48 seeds. The research results showed a real interaction between the combination of clay doses and green fertilizer and the number of leaves. The best treatment combination was a green fertilizer dose of 100 g/seedling with a clay dose of 150 g/seedling. Providing clay in the beach sand planting medium influences the growth of oil palm seedlings in the pre-nursery, as seen from the parameters of leaf area, fresh root weight, root dry weight, and number of secondary roots. The best dose of clay is 200 g/seedling. Providing green fertilizer influences the growth of oil palm seedlings in the pre-nursery. Based on seedling height, number of leaves, fresh weight of the crown, fresh weight of the roots, and stem diameter, the best dose of green fertilizer is 50 g/seedling. Keywords: beach sand; clay; green manure; palm oil; pre-nursery.